Realizacja rządowego programu integracji społeczności romskiej w Polsce na przykładzie województwa lubuskiego - Krzyżanowski, Piotr Jacek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The realization of the governmental program of the integration of the Roma people in the Lubuskie voivodeship is characterized by the understanding of and respect for the Gypsy identity. The assistance that Gypsies receive makes their situation better, especially in the sphere of education. What is more, in the local environment there has been fewer conflicts and troubles between the Roma people and their neighbors. The positive effects of the governmental program result from the dialogue between governmental institutions and the recipients of the program.
The Realization of the Governmental Program of the Integration of the Roma People in Poland. The case of the Lubuskie Voivodship
Keywords: Gypsies in the Lubuskie region; integration; ethnic minorities